DAMPAK PEMALSUAN PUTUSAN MAHKAMAH KONSTITUSI - Wahid, Abdul (JURNAL KONSTITUSI, 2011)
The effect of the falsification through the constitutional court verdict not only will make the image of polri, as a competent aspect in maintaining it, become better or worse compared to nowadays condition, but also can give a very big influence to the publiccredibility through the constitutional court and the lawstate. A transparent, objective and holding on to the juridical norms investigation through anybody being suspected to get included becomes the key factor determining the form of public evaluation and trust to polri, the constitutional court and the law state.Â